EVALUASI KEBIJAKAN PARIWISATA BERKELANJUTAN BERBASIS SOUND GOVERNANCE DI KAWASAN DANAU TOBA - Hajar, Siti; Syafrizal (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
Lake Toba area as one of the national super priority tourism destinations (DPSP) faces challenges in realizing sustainable tourism management. This study is important because it focuses on the need for evaluation of tourism policies that not only emphasize aspects of physical and economic development, but also integrate sound governance principles such as transparency, accountability, participation, effectiveness and responsiveness in every stage of its formulation. The purpose of this study is to evaluate the implementation of sustainable tourism policies in the Lake Toba area with a good governance approach as an analytical framework. The method used in this study is a qualitative approach with thematic analysis and SWOT analysis. The results of the study indicate that although there has been progress in infrastructure development and tourism promotion, the application of sound governance principles is still partial and has not been integrated systemically. The main weaknesses lie in the weak coordination between institutions, limited participation of local communities in decision-making, and the suboptimal public accountability mechanism. These findings emphasize the importance of reformulating sustainable tourism policies in the Lake Toba area through a more inclusive, collaborative, and data-based sound governance approach.